Percutaneous large‐bore axillary access is a safe alternative to surgical approach: A systematic review. Issue 7 (14th September 2020) - Southmayd, Geoffrey; Hoque, Azizul; Kaki, Amir; Tayal, Rajiv; Rab, S. Tanveer
Abstract: Objectives: To systematically review relevant literature regarding cardiovascular outcomes of large‐bore axillary arterial access via percutaneous and surgical approaches. Background: In patients with severe peripheral arterial disease (PAD) undergoing cardiac interventions, large‐bore femoral access may be prohibitive. The axillary artery provides an alternative vascular access for transcatheter aortic valve replacement (TAVR) or mechanical circulatory support. There have been limited comparisons of percutaneous transaxillary (pTAX) approach with the more traditional surgical transaxillary (sTAX) approach. Methods: Pubmed and Medline databases were queried through January 2019 for studies describing pTAX or sTAX approaches with TAVR or Impella insertion. Primary outcomes were access‐related mortality, 30‐day mortality, stroke, major vascular complications, and major bleeding. Results: One hundred and fifty five studies were reviewed, with additional unpublished data from 1 institution. Twenty‐two studies met the inclusion criteria. Patient data was heterogeneous, with 69% TAVR and 31% Impella use in the pTAX group, and 96% TAVR and 4% Impella use in the sTAX group. There was more cardiogenic shock in the pTAX group. When compared to surgical approach, the percutaneous approach had similar 30‐day mortality for TAVR (5.6% vs 4.6%, OR non‐significant) and Impella (43.4% vs 38.6%, OR non‐significant), similar stroke rates (4.3% vs 4.2%, OR non‐significant), similar major vascular complications (2.8% vs 2.3%, OR non‐significant) and less major bleeding (2.7% vs 17.9%, OR significant). Conclusions: Data suggests large‐bore pTAX access has similar 30‐day mortality, stroke rates, and major vascular complications as sTAX access, with less major bleeding. Additional studies are needed to validate results.